Pertanggungjawaban Hukum Terhadap Direksi yang Melakukan Penggelapan Aset Pada Perusahaan yang Dinyatakan Pailit (PT. Bumi Asih Jaya) - Tumpal Utrecht Napitupulu; Sunarmi Sunarmi; Mahmul Siregar; Mahmud Mulyadi (Universitas Sumatera Utara, 2019)
Abstract. A Board of Directors acts carefully in carrying out its duties (duty of care). In addition, in carrying out its duties, a Board of Directors may not take advantage of himself for the company (duty of loyalty). Moreover, the Company which is engaged in the insurance industry, which currently shows a tight growth because the public is more aware of insurance as part of risk management that must be prepared as early as possible for the protection of health, life, property, business / business, and others. The research aims to find out and understand the insolvency of insurance companies based on positive law in Indonesia, the position and responsibility of the directors of insurance companies that have been declared bankrupt and the responsibilities of directors who embezzle the assets of insurance companies that are declared bankrupt. The research uses normative juridical research and the nature of analytical descriptive research. Method of legislation approach (statutedapproach). The sources of library data and documents are obtained from primary, secondary and tertiary legal materials. The data collection technique is library research. Analyze data with a qualitative approach. The Company's bankruptcy occurred because the Directors' errors and omissions were insufficient to pay all of the Company's obligations in bankruptcy, each member of the Board of Directors was jointly responsible for all obligations that were not repaid from the bankrupt assets. The legal consequences of directors who embezzled the assets of insurance companies that were declared bankrupt in the form of termination of directors for embezzlement of insurance company assets, directors returned money from embezzlement of company assets, directors of bankrupt companies may not be directors in other companies and detained directors in Darkening assets. The actions of the Board of Directors of PT Asuransi Jiwa Bumi Asih Jaya carried out embezzlement of assets on the company declared bankrupt because of its ignorance or because of intentions. Legal responsibility for directors who commit asset embezzlement on companies declared bankrupt (PT. Bumi Asih Jaya) found criminal elements, namely money wiping and fraud, Directors can be punished with imprisonment or criminal penalties (Article 372 and Article 378 of the Criminal Code) accountability to his personal assets (Article 97 paragraph (3) of the Company Law) so that the members of the Board of Directors concerned are personally responsible in accordance with Article 101 paragraph (1) and (2) of the Company Law. Keywords: accountability of directors, embezzlement of assets, bankruptcy